Ebola virus – from neglected threat to global emergency state - Pacheco,Daniela Alexandra de Meneses Rocha Aguiar (2016)
SUMMARY Objective: This review aims to update knowledge about Ebola virus disease (EVD) and recent advances in its diagnosis, treatment and prevention. Method: A literature review was performed using the following databases: ISI Web of Knowledge, PubMed, IRIS, Scopus and the websites of the CDC and the WHO. Additionally, we have included articles and reports referenced in the basic literature search, and news that were considered relevant. Results: The Ebola virus, endemic in some parts of Africa, is responsible for a severe form of hemorrhagic fever in humans; bats are probably its natural reservoir. It is an extremely virulent virus and easily transmitted by bodily fluids. EVD's complex pathophysiology, characterized by immunosuppression as well as stimulation of an intense inflammatory response, results in a syndrome similar to septic shock. The diagnosis is difficult due to the initial symptoms that mimic other diseases. Despite the high mortality rates that can amount to 90%, a prophylaxis (chemical or vaccine) or effective treatment does not exist. Two vaccines and experimental therapies are being developed for the prevention and treatment of EVD. Conclusion: Although the virus is known for about 40 years, the lack of knowledge obtained and the disinterest of government authorities in the countries involved justify the state of emergency currently exists regarding this infectious agent. Only the coordination of multiple entities and the effective commitment of the international community will facilitate the control and effective prevention of EVD.